Implications of the EU Emissions Trading System (ETS) on European container routes: A carbon leakage case study - Sotiria Lagouvardou; Harilaos N. Psaraftis (Maritime Transport Research, 2022)
The paper focuses on the impacts of the inclusion of the maritime sector in the EU Emissions Trading System (ETS). The enforcement of a regional Market-Based Measure (MBM) such as the EU ETS may provide financial incentives to shipping operators to reconfigure their networks and avoid voyages inside the European Economic Area (EEA). This paper investigates the risk of container vessels engaging in evasive port calls by replacing EEA transshipment hubs with nearby non-EEA competitors. We perform a cost–benefit analysis that calculates the cost of EU Allowances (EUAs) for several international services and compares it with a relocation scenario. Our case studies focus on the Piraeus–Izmir and the Algeciras–Tanger Med scenarios and identify the EU carbon price turning point that will render the switch of the transshipment hubs a cost-effective choice for the operator. The results show that the preference of a non-EEA hub will become attractive for carbon prices well below 25 EUR per metric ton of CO2. Further, in all cases, the hub switch results in a rise in the overall carbon emissions attributed to the service which amplifies the risk of carbon leakage. Our results show that the relocation would lead to revenue loss for the EU ETS and penalization of the EEA transshipment hubs in close proximity with hubs outside the EEA, thus posing a threat to their economic activity and development.